SYSTEM THERAPY OF PSORIASIS IN CHILDREN (PART I) - L. S. Namazova-Baranova (Vestnik Dermatologii i Venerologii, 2017)
We include a review of modern methods of systemic therapy of psoriasis in children, indications for which are moderate and severe forms of psoriasis with PASI > 10, skin pathological process that is uncontrollable with topical drugs, skin lesions with functional localization (lesions of genitals, palms and soles, facial skin), erythrodermic psoriasis, pustular psoriasis, psoriatic arthritis. We provide information on the techniques of narrow-band phototherapy (UVB 311 nm) that are used in the treatment of psoriasis in children. We provide data on efficacy, safety, necessary monitoring of clinical and laboratory indicators, peculiarities of vaccination during treatment of children with acitretin, methotrexate, cyclosporine.